The Forgiveness to Come : The Holocaust and the Hyper-Ethical - Banki, Peter (Book collections on Project MUSE., 2018)
This text addresses the difficulties posed by the Holocaust for a thinking of forgiveness inherited from the Abrahamic (i.e., monotheistic) tradition. As a way to approach these difficulties, it explores the often radically divergent positions in the debate on forgiveness in the literature of Holocaust survivors.